MASALAH DAN ISU KEBIJAKAN KESEHATAN DI INDONESIA - Nasution, Irfan Sazali; Khoirunnisa, Fazri; Dewi, Saharani Saari; Siregar, Aspadil; Ayu Stiawan, Yolanda Ajeng (JURNAL KESEHATAN INDRA HUSADA, 2024)
Health problems in Indonesia are still considered complex, especially related to disparities in access and quality of health services. This research aims to analyze health policy in Indonesia, especially the implementation of National Health Insurance (JKN), as well as identifying challenges and opportunities for improvement. The method used is a literature study by analyzing various sources related to health policy in Indonesia. The research results show that the implementation of JKN has expanded the reach of medical services to make them more accessible to various levels of society, but there are still gaps in the quality and distribution of services in various regions. Key challenges include limited resources and lack of coordination between institutions. Health policy reform has brought positive changes, but still requires continuous improvement. Multisector collaboration has proven effective in addressing social determinants of health. This research recommends strengthening the referral system, developing an integrated health information system, and implementing policies that are more responsive to specific regional needs. For further research, it is recommended to focus on evaluating the JKN program and the effectiveness of cross-sector collaboration in improving public health status.